Tata Kelola dan Performa Finansial Perusahaan di Indeks LQ45 - Wijaya, Suwito; Ugut, Gracia Shinta S. (Universitas Proklamasi 45, 2024)
This study focuses on exploring the relationship between governance mechanisms and corporate financial performance in non-financial business entities in Indonesia. The analysis was conducted by applying a regression model to panel data involving companies listed on the LQ45 index on the Indonesia Stock Exchange from 2013 to 2022. The variables tested in the context of corporate governance include: managerial ownership, institutional ownership, independence of commissioners, board size, and audit committee meetings. This study assesses corporate financial performance using Return on Assets (ROA) and Tobin's Q. The findings show a statistically significant positive effect between institutional ownership and corporate financial performance, both based on ROA and Tobin's Q indicators. It is hoped that these findings can provide a new perspective regarding how various elements of corporate governance impact financial performance and contribute to the formulation of corporate governance policies and practices in Indonesia.